2017
DOI: 10.3390/su9101916
|View full text |Cite
|
Sign up to set email alerts
|

The Emissions of Carbon Dioxide, Methane, and Nitrous Oxide during Winter without Cultivation in Local Saline-Alkali Rice and Maize Fields in Northeast China

Abstract: Agricultural ecosystems are important contributors to atmospheric greenhouse gasses (GHGs); however, in situ winter emission data in saline-alkali fields are scarce. Gas samples were collected during different periods, from three rice (R1-R3) and three maize (M1-M3) fields with different soil pH levels and salinity conditions. Carbon dioxide (CO 2 ) emissions in the rice and maize fields decreased with decreasing temperature during the freezing period and increased with the rising temperature during the thawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…SOC is used as substrate for microbial respiration and is therefore vital to the process [42]. We found that soil MBC and DOC decreased under three years of warming in the boreal peatland.…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 66%
“…SOC is used as substrate for microbial respiration and is therefore vital to the process [42]. We found that soil MBC and DOC decreased under three years of warming in the boreal peatland.…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 66%
“…The annual mean temperature is about 4.5 • C, the lowest temperature is in January (the extreme minimum temperature −36.1 • C), and the highest temperature is in July (the extreme maximum temperature 37 • C). Annual precipitation is between 400 mm and 500 mm [32].…”
Section: Study Sites and Sampling Designmentioning
confidence: 99%
“…The annual mean temperature is about 4.5 °C, the lowest temperature is in January (the extreme minimum temperature -36.1 °C), and the highest temperature is in July (the extreme maximum temperature 37 °C). Annual precipitation is between 400 mm and 500 mm [32]. Four plots (P1, P2, P3, and P4) with different saline-alkali stresses were selected after preexperiments and initial data analysis of the project (Table 1).…”
Section: Study Sites and Sampling Designmentioning
confidence: 99%
“…Global warming is receiving more and more attention because of the series of threats it poses, like sea-level rise, land area decline, extreme climates, and food supply shortages, which challenge the sustainable development of eco-environments and social economy [1]. Greenhouse gas (GHG) emissions, including carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O), are responsible for global warming, owing to the greenhouse effects.…”
Section: Introductionmentioning
confidence: 99%
“…SIC is classified as two central units stored in soil, namely, lithogenic inorganic carbon (LIC), inheriting from the parent material, and pedogenic inorganic carbon (PIC), resulting from the precipitation of carbonate ions. The formation of pedogenic carbonate, shown in Equations (1) and (2), can either be a source or sink of C [16]. In the input or output of soil, C is transformed in the process of precipitation.…”
Section: Introductionmentioning
confidence: 99%